Cesarean scar pregnancy managed with local and systemic methotrexate: A single center case series. (July 2019) - Naeh, Amir; Shrim, Alon; Shalom-Paz, Einat; Amir, Michal; Hallak, Mordechai; Bruchim, Ilan
Abstract: Objective: To report the efficacy of combined systemic and local methotrexate treatment for cesarean scar pregnancy and review data from selected, similar case series. Study design: A retrospective case series of 12 patients with cesarean scar pregnancy treated in a university hospital between 2014 and 2018. The intervention was combined treatment of systemic and local methotrexate. Results: Twelve patients were treated with combined systemic and local methotrexate. Clinical characteristics, clinical course and treatment efficacy were evaluated. Mean gestational age at diagnosis was 7.5 weeks (range 5.9–9.1). βhCG levels at diagnosis ranged from 1581 to 345, 427 U/L with a mean of 77, 795 U/L. All 12 patients were successfully treated without surgical intervention and with no significant side-effects. Mean hospitalization duration was 9 days (5.8–12.6) and mean time to normalization of βhCG levels was 98 days (63–132). Conclusions: Treatment of cesarean scar pregnancy with a combination of systemic and local methotrexate was effective and safe. Although the treatment course tends to be longer than with other modalities, this protocol offers excellent success rates, with fertility preservation and few complications.